Integrated local development in Mediterranean marginal territories: The case study of Casentino (Italy), Algarve (Portugal) and Corse (France) - Andrea Ricci; Mario Biggeri; Andrea Ferrannini (REGION, 2019)
Today, Mediterranean marginal territories are facing tremendous challenges but at the same time they have relevant endogenous resources, which are often underutilized and unexploited and that could be pivotal for the strategic recovery and economic and social development of the whole European territory. In the last decades, they have been characterised by a progressive abandonment in favour to urban areas, with consequent high social costs such as the hydrogeological instability, degradation and soil erosion. This research investigates the potential active role of Mediterranean 'marginal territories' with respect to the re-formulation, adaptation, interpretation and implementation of the European development policies. The paper aims to verify the idea that Mediterranean marginal territories, in the sense of weak, mountainous and inland, could take part at the construction of their own development trajectories and actively contribute to the harmonious development of Europe, creating new jobs opportunities and stable development patterns. Moreover, the paper aims to formulate policy implications and strategies for the studied areas and for Mediterranean marginal territories more in general.~The structure of this paper starts from general theoretical arguments and a short description of European policies for development; it follows with the diagnostic analysis of three local territorial contexts - i.e. Casentino (Italy), Algarve (Portugal) and Corse (France) - and then it comes back on the general European issues proposing implications and lessons learnt in the analysis of the development processes at the local level.
Keywords: 330; European and Mediterranean marginal territories; sustainable human development; territorial cohesion; Casentino; Algarve; Corse